Ideology, Nationalism and Law: Legal Tools for an Ideological Machinery in Latvia - Šulmane, Dace (University of Wroclaw. Faculty of Law, Administration & Economics, 2015)
For around 25 years Latvia has moved further and further away from Soviet Marxism-Leninist state ideology and has successfully re-integrated with European legal culture. It is obvious that the term ‘ideology’, due to its historical Soviet context, has a mostly negative colouring even nowadays. Integration within the European Union and the implementation of social and political programs and concepts have led to questions raised about leading contemporary ideology (ies) and its (their) role in the development of Latvia’s legal system. The issue of ideologies becomes more complicated and unclear when regarding specific legal reforms or Parliament`s drafts of laws. The article will explore the elements of different ideologies manifested in the Latvian legal corpus and try to identify how the contemporary legislator (the Saeima) deals with the challenges of competing ideologies in the context of what remains post-Soviet legal thinking.
Keywords: Łotwa; ideologia; postsowieckie myślenie prawnicze; Saeima